Analisis Hambatan Belajar Mahasiswa pada Mata Kuliah Statistik - Yohanes Briyan Vincesius Mendrofa; Angela Br Surbakti (Yayasan Literasi Sains Indonesia, 2023)
Education is an effort to make sense of understanding and the promise of learning so that it can combine the qualities of life. For this reason, it is necessary to minimize it so that there are no obstacles to learning activities. Obstacles are a role in the process of learning language and language to gain knowledge. Therefore, samahawa is aware of being able to fall behind in learning which has an impact on the obstacles that are left behind. This research focuses on qualitative descriptive research which is also used to analyze learning obstacles in statistics courses. Studying statistics courses is very crucial for students during their time when they are required to study, process, analyze and interpret data to complete their thesis, thesis and/or dissertation. Simply put, statistics in education involve the regular collection of both raw and unprocessed data. The subject of this presentation is the level II and III health news management study program which is attended by 30 people at STIKes Santa Elisabeth Medan. This research is a cooperative company that is secure in its location to reveal the things that have become a factor that hinders learning in the world in the eyes of College Statistics.